Biodegradable film mulching promotes better soil quality and increases summer maize grain yield in North China Plain. Issue 13 (10th November 2023) - Li, Ming; Zhang, Qingfen; Wei, Shiyu; Liu, Zhendong; Zong, Rui; Jin, Tuo; Zhang, Mingming; Sun, Chitao; Li, Quanqi
ABSTRACT: Soil pollution caused by the residual polyethylene film is a potential threat to agricultural sustainability. Biodegradable films are generally effective alternatives to reduce this pollution. However, soil quality changes responding to continuous biodegradable film mulch are still unclear. To reveal the accumulative effects of biodegradable film mulch on soil quality, we conducted a positioning experiment from 2016 to 2019 in North China Plain (NCP). Four treatments, including transparent polyethylene film mulching (PM), transparent biodegradable film mulching (TM), black biodegradable film mulching (BM), and non-mulching (CK) were employed. The results showed that compared with CK, both BM and TM treatments significantly reduced soil bulk density and increased soil microbial activity and soil enzyme activity; however, BM and TM did not affect soil nutrient content. Compared with CK, BM treatment significantly increased soil quality index (SQI) by 7.2% (in 2019) due to higher soil fertility content and bioactivity; however, TM and PM treatments decreased SQI by 3.2% and 3.8%, respectively. Besides, compared with CK, BM significantly enhanced summer maize grain yield by 30.35%. Therefore, black biodegradable film is a potential alternative to polyethylene film to improve soil quality and maize production in NCP.